(untitled) (Raparin Journal of Humanities (RJH), 2022)
The population, could be considered as the main element of civilization, has provided the regions with a social and civilized characteristic. For example, as they have impacted the events themselves and have been a crucial role in creating them. They have always been influenced by natural and humanitarian incidents. So as a social creature, the principle of population has continued to change in terms of quantity and quality. Increasing and decreasing the population is one of the phenomena that has never been separated from elements of the population. It seems that the Kurdish areas as an old center of life and civilization have faced Weal and woe at the same time changes have happened to the population especially in the Abbasid era which was a time of events and changes. This time is the period of research on the growth and raising of the population of Kurdish areas based on historical information from the sources that focuses on the natural and human causes of population growth with its different components. The study consists of two main topics, results, and a list of sources including the principles of population enlargement and the reasons for their increase. It is based on many sources and new academic research to provide a small service to the Kurdish scientific and historical process.